Kaedah Perbincangan dalam Pengajaran Pendidikan Islam di Sekolah Rendah - Abu Bakar, Nor Syahirah; Che Noh, Mohd Aderi (Jurnal Pendidikan Nusantara, 2022)
The method of conversation is one of the mediums used by teachers in achieving their teaching objectives. The results of the discussion sessions made by students in the group succeeded in achieving student understanding of the lessons being taught. At the same time, this discussion method can be used for all subjects based on the teacher's creativity. This study will focus on conversation methods in the teaching of Islamic education in low schools. This study aims to identify the concept of the discussion method, how to apply the conversation method in teaching Islamic education in ordinary schools, and review the effectiveness of the conversation method. This study was carried out using a qualitative approach based on library studies and informal interviews with bright teachers of low school Islamic education. Document analysis and independent studies are also used as references. The study results found that this discussion method was suitable for use in teaching Islamic education at the low school level. The teacher's use of correct conversational methods gives the impression of understanding, motivation, and academic improvement in student learning.